Ethics, Public Policies, Financial Markets, and Institutions: New Global Policies, Financial, and Social Crises - Ioannis N. Kallianiotis (Current Topics on Business, Economics and Finance Vol. 1, 2023)
In this chapter are discussed some ethical issues regarding the financial market, the institutions, and the latest public policies, monetary and fiscal one. Morality and ethics are very important for a society and a nation and reveal the wellbeing of its structure, its business, its institutions, its policies, its government, its education, its value system, and its future existence. All these foreshadow the future of the nation and the wellbeing of its citizens and future generations. In a country where ethics have been abandoned, we can, from historical experience, easily to predict its future. It has no future. A democratic government has to impose fair regulations, laws and order, to keep the entire society at an advanced ethical level, after all this knowledge of thousands of years of history, civilization, experience, tradition, and revelation. Public policy (both monetary and fiscal), institutions, organisations, and agencies must all be guided by ethical, fair, and moral principles. The latest two financial, economic, and social crises, especially, the last one, the suspicious coronavirus (COVID-19) pandemic, the lockdowns, the elections irregularities, could have been avoided or curtailed if the responsible generators (“elites”) of these events were ethical and respectful towards the other people, other nations, and to our democratic system. But, because they are acting in favor of their self-interest and against social interest, they have to be controlled by the independent sovereign nations and democratic governments of the world.